Penerapan Media Scrapbook Berbasis Indigeneousasi untuk Peningkatan Literasi Membaca Siswa Kelas V SDN 26 Singkawang Barat - Rimi, Rimi; Fitri Fitri; Emi Sulistri (FKIP, Universitas Palangka Raya, 2024)
This research aims: 1) To identify whether there is an increase in reading literacy through indigenousization-based scrapbook media for class V students at SDN 26 Singkawang Barat, 2) To describe the level of implementation of indigenousization-based scrapbook media for increasing reading literacy for class V students at SDN 26 Singkawang Barat, 3) To describe the level of student response to indigenousization-based scrapbook media to increase the reading literacy of class V students at SDN 26 Singkawang Barat. This type of research is quantitative research using the Pre Experimental Design method. The population in this study was all class V of SDN 26 West Singkawang. The sample uses Saturated Sampling. Data collection techniques used student reading literacy essay tests, media implementation observations and student response questionnaires. The data analysis technique uses N-Gain, percentage of implementation observations and percentage of student response questionnaires. The research results show 1) There is an increase in students' reading literacy after implementing indigenous-based scrapbook media with an average score of 0.67 with medium criteria, an N-Gain Score percentage of 67% with the interpretation of effectiveness being quite effective. 2) The level of implementation of indigenousization-based scrapbook media was carried out well as seen from the percentage at the first meeting of 98.61% with very good criteria and the percentage at the second meeting was 97.22% with very good criteria. 3) There is a positive response to indigenous-based scrapbook media to increase students' reading literacy. With a student response percentage of 83% with very good criteria. Based on the results of research data calculations, it can be concluded that indigenous-based scrapbook media has increased the reading literacy of class V students at SDN 26 Singkawang Barat.